Rekomendasi Jenis Vaksin Covid-19 Untuk Meminimalisir Kejadian Ikutan Pasca Imunisasi (KIPI) Berbasis Mobile - Eka Rahmawati; Akhmad Syukron (Jurnal Teknologi Informasi dan Terapan, 2022)
The Covid-19 pandemic is one of the events that had an impact on life. Various steps have been taken by the government to prevent the spread. The number of cases that continues to increase makes various policies implemented. One way to do this is by giving the Covid-19 vaccine. Vaccination is still being carried out until the community gets the third dose of the vaccine (booster). Vaccination can give Post Immunization Adverse Events (AEFI). The AEFI experienced can differ from one person to another. Therefore, the Covid-19 vaccine type recommendation system can help to minimize the presence of AEFIs by providing the type of vaccine that is by health conditions.